A Systematic Review of the Relationship Between Human Resource Management, Ethnic Diversity, Job Satisfaction, and Organizational Performance. - Daberechukwu, Nnamoko Faith; Kamarudin, Mohd Fauzi (The journal of contemporary issues in business and government, 2021)
The employee is an integral part of any organization, the job performance of the employee is linked to his/her job satisfaction, and this influences the employee’s level of motivation on the job which directly reflects on the organizational productivity. The human resource management (HRM) has the key role of ensuring that the rights of each employee are respected as well as ensuring the protection of interests and job satisfaction of the employees. This study seeks to examine the relationship between the human resource management, ethnic diversity, job satisfaction, and organizational productivity, highlighting the role of the human resource management on the management of ethnic diversity, job satisfaction as well as organizational performance. This paper is based on previous research studies data from google scholar from the year 2010 to 2020. 19 articles were found related to the search keywords. This paper would be relevant for further study on the relevant areas to tackle to improve the organizational performance as well as its productivity.